SATUAN POLISI PAMONG PRAJA SEBAGAI PELINDUNG MASYARAKAT - Dedy Suhendi (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2019)
The purpose of this paper is to better understand and know what are the main tasks and functions of the Civil Service Police Unit, especially the police officers at the district level. As is known together, Satpol PP is an agency in the area that was formed to enforce Regional Regulations and Regulations of the Head of Region, to carry out public order and peace and to protect the community. The position of the district Satpol PP is under the Regent and administratively and operationally responsible to the Regent. In this paper the author will focus on the task of Satpol PP as protection of the community. Each region has different characteristics and experiencesdifferent disaster problems, ranging from floods, landslides, fires, droughts and so on. Disasters can be in the form of disasters caused by humans or because of nature and these events occur almost every year, even in some areas known as flood-subscribed areas. Writing this script is the result of a conceptual study, so the results of this writing are expected to be useful especially for readers so that they understand better what the Satpol is. Instruments for retrieving data are taken from several reference sources, electronic media and direct observations of the results of the author’s experience in the area. Keywords: Satpol pp, Community Protection and Disaster Mitigation